ERROR ANALYSIS OF EFL STUDENTS IN TRANSLATION: A STUDY AT EVEREST ENGLISH COURSE, SURABAYA - Annisa Triana Flyandjono; M. Afifulloh (Loquēla (Journal of Linguistics, Literature, and Education), 2025)
This paper aims to highlight pragmatic failure and to analyze the translation errors made by EFL (English as a Foreign Language) students at Everest English Course, Surabaya. The researcher focuses on the mistakes often occurring in English classes. The method of this study is descriptive qualitative, which focuses on describing student's translation errors. The acquisition uses the theory introduced by (Corder, 1967; Richards, 1971) to identify the types of interlingual or intralingual matters. The research involves 25 randomly selected students of varying ages (male and female) as subjects of this examination. They were given some translation tasks for seven phrases and sentences without looking up the meaning in a dictionary. The most frequent mistake appeared in the phrase "Thank you before," produced by 80% of students. Other recurring errors included "Thanks God" and incorrect adjective forms like "I am boring". The findings indicate that the students' errors were strongly influenced by the structure of their first language (L1). The results suggest that teaching translation should focus more on fixed expressions, pragmatic usage, contrastive understanding of sentence patterns, and pedagogical implications.